The Multisensory Nature of Verbal Discourse in Parent–Toddler Interactions. Issue 5 (16th November 2016) - Suanda, Sumarga H.; Smith, Linda B.; Yu, Chen
ABSTRACT: Toddlers learn object names in sensory rich contexts. Many argue that this multisensory experience facilitates learning. Here, we examine how toddlers' multisensory experience is linked to another aspect of their experience associated with better learning: the temporally extended nature of verbal discourse. We observed parent–toddler dyads as they played with, and as parents talked about, a set of objects. Analyses revealed links between the multisensory and extended nature of speech, highlighting inter-connections and redundancies in the environment. We discuss the implications of these results for our understanding of early discourse, multisensory communication, and how the learning environment shapes language development.